Effect of Order of Reagents Addition on Optical and Structural Properties of CdS Quantum Dot Prepared by Chemical Bath Deposition Technique - Nwabue, F. I.; Oroke, E. C.; Onah, D. U.; Nworie, F. S.; Ikele, I. I. (Iraqi Journal of Science, 2024)
Cadmium sulfide quantum dots were synthesized and deposited on glass substrates by chemical bath deposition (CBD) technique using cadmium sulfate and thiourea solutions in the presence of a 4,4’-(1,2-ethanediyldinitrilo)bis-(2-pentanone) (EDDBP) tetradentate ligand as a complexing agent. The order of reagents addition was varied to deposit films that were characterized for their surface morphological, optical, structural, and solid-state properties using a scanning electron microscope (SEM), a UV-visible spectrophotometer, an X-ray diffractometer (XRD), and Brunauer-Emmet-Teller (BET) analyses. The optimal condition for film deposition using the normal sequence of reagents addition was found at pH 8-12 and 298-353 ± 1K and gave films of 2.40-321.06 nm thickness, while the variation in the order of reagents addition gave improvements in the film properties. The optical properties and the observed direct band gaps (1.75-3.16 eV) of the films suggest usage in electroluminescent and solar cell devices since they have a first-order transition. The XRD patterns of the quantum dots indicated hexagonal wurzite structures, while the BET confirmed their mesoporous and nanonature.